Von Hippel-Lindau syndrome and renal tumours: radiological diagnostic and treatment options. A case report and literature review - Untanas, Audrius; Trakymas, Mantas; Lekienė, Indrė; Briedienė, Rūta (Acta medica Lituanica, 2020)
Background. Von Hippel-Lindau disease (VHL) is a rare autosomal dominant syndrome diagnosed for 1 out of 36000–45000 newborns and 90% of the patients have a clinical manifestation before 65 years of age. Affected individuals have an increased risk of developing tumours in several organs or their systems. The most common tumours are retinal or central nervous system hemangioblastomas (60–80%) and VHL-associated renal lesions. Contrast-enhanced computer tomography (CECT) is the gold standard for the diagnosis and characterization of renal tumours. The best treatment option for VHL syndrome-caused renal tumours are nephron-sparing treatment techniques (cryotherapy, radiofrequency, or microwave ablation), which require imaging control. All these innovative treatment techniques are extremely important for VHL patients, because they increase the quality of life by staving off renal dialysis and preventing distant metastases. Case report. Our case report presents a 16-year-old female with multiple renal cysts observed on ultrasound examination and clinically and molecularly diagnosed with Von Hippel-Lindau syndrome (deletion of the entire VHL gene). After that, for past 11 years multiple renal tumours were removed by cryoablation and patient monitoring on contrast-enhanced magnetic resonance (MRI) and CECT control scans was conducted. Conclusions. Active multidisciplinary patient follow-up, routine radiological examinations, and correct treatment tactics allow controlling the progression of renal cell carcinoma and other tumours associated with VHL syndrome, maintaining a normal organ function for a long time, and preventing distant metastases and fatal disease outcomes.
Keywords: VHL syndrome; clear cell RCC; cryoablation